Perineural Invasion of the Intratemporal Facial Nerve: How Far Proximally Do We Chase the Positive Margin?. Issue 10 (18th December 2021) - Page, Joshua Cody; Nader, Marc-Elie; Knackstedt, Mark; Roberts, Dianna; Gidley, Paul W.
Abstract : Objective: To determine recurrence patterns in patients with head and neck cancers requiring facial nerve sacrifice and to determine the optimal management of the positive proximal facial nerve margin. Study design: Case series with chart review. Setting: Tertiary care center. Patients: One hundred fifty-five patients with head and neck malignancies who underwent sacrifice of the facial nerve between March 1, 1999 and October 31, 2020. Demographics, preoperative facial nerve function, prior oncologic treatment, histologic type, operative details, adjuvant treatment, recurrence patterns, and overall survival were reviewed. Main outcome measures: Recurrence rates and recurrence location. Results: Thirteen patients (8%) had positive proximal margins on final pathologic evaluation. Six of 13 (46%) experienced disease recurrence. No disease recurred proximally along the facial nerve. The recurrence rate was 26% for negative proximal facial nerve margins. Segments of the facial nerve biopsied included: extratemporally (n = 78), at the stylomastoid foramen (36), mastoid segment (22), second genu (7), tympanic (6), geniculate (3), labyrinthine (1), and IAC (2). Median patient follow-up was 30.3 months. Conclusions: Our data suggest that a conservative approach to a positive proximal facial nerve margin is optimal with respect to operative planning, patient morbidity, and disease recurrence patterns. Recurrence proximally along the facial nerve is an exceedingly rare event and the necessity of biopsy proximal to the geniculate ganglion, and in some cases even to the second genu, is called into question.